Roles of lncRNAs related to the p53 network in breast cancer progression - Song, Jiarui; Cui, Qiuxia; Gao, Jidong (Frontiers in Oncology, 2024)
The p53 is a crucial tumor suppressor and transcription factor that participates in apoptosis and senescence. It can be activated upon DNA damage to regulate the expression of a series of genes. Previous studies have demonstrated that some specific lncRNAs are part of the TP53 regulatory network. To enhance our understanding of the relationship between lncRNAs and P53 in cancers, we review the localization, structure, and function of some lncRNAs that are related to the mechanisms of the p53 pathway or serve as p53 transcriptional targets.